包含至少一种溶于水性介质且具有改善肠道吸收的药物可接受的依拉贝特盐的组合物 (2023)
本发明涉及一种组合物，该组合物包含作为活性成分的依拉贝特(elafibranor)的药物可接受的盐，其特征在于依拉贝特的药物可接受的盐选自胆碱盐、乙醇胺盐、二乙醇胺盐、赖氨酸盐、哌嗪盐、钙盐或氨丁三醇盐中的至少一种。更具体地，本发明涉及依拉贝特盐的使用，与基本形式的依拉贝特相比提高了稳定性和溶解性。这些盐使得构建各种有利形式的药物制剂(如静脉注射或经肠途径的制剂)成为可能，其具有更快和更少的可变吸收，因此具有更好的生物利用度。 A composition comprising, as an active principle, a pharmaceutically acceptable salt of elafibranor, characterised in that the pharmaceutically acceptable salt of elafibranor is chosen from at least a salt of choline, of ethanolamine, or of diethanolamine, or of L-lysine, or of piperazine, or of calcium, or of tromethamine. More particularly, one or more embodiments relate to the use of elafibranor salts with a view to improving stability and solubility compared with elafibranor in the basic form thereof. These salts make it possible to establish pharmaceutical formulations in various advantageous forms as intravenous injections or formulations by enteral route having quicker and less variable absorption and consequently better bioavailability.